Synthesis, Characterization and Biocompatibility Evaluation of Novel Chitosan Lipid Micro-Systems for Modified Release of Diclofenac Sodium - Ana-Maria Raluca Pauna; Liliana Mititelu Tartau; Maria Bogdan; Andreea-Daniela Meca; Gratiela Eliza Popa; Ana Maria Pelin; Cristian Ilie Drochioi; Daniela Angelica Pricop; Liliana Lacramioara Pavel (Biomedicines, 2023)
The purpose of our study was the obtaining, characterization and biocompatibility estimation of novel carrier systems for diclofenac. Diclofenac is a potent nonsteroidal anti-inflammatory drug with frequent gastrointestinal side effects, impairing the quality of the patient’s life. Original diclofenac-loaded micro-vesicles coated with chitosan were prepared and physico-chemical analyzed. We investigated their in vitro hemocompatibility and in vivo biocompatibility in rats. The animals were treated orally as follows: group 1 (Control): distilled water 0.3 mL/100 g body weight; Group 2 (CHIT): 0.3 mL/100 g body weight 0.5% chitosan solution; Group 3 (DCF): 15 mg/kg body weight diclofenac; Group 4 (DCF-ves): lipid vesicles loaded with diclofenac 15 mg/kg body weight. Blood samples were collected for assessing: red blood cells, hemoglobin, hematocrit and leukocyte formula. A series of specific parameters of the liver and kidney function, some markers of immune defense, as well as the activity of some enzymes involved in oxidative processes, were also investigated. At the end of the experiment, the animals were sacrificed and fragments of liver, kidney and stomach were collected for histopathological examination. No blood hemolysis was evidenced by the in vitro test with the administration of diclofenac vesicles. The animals treated with diclofenac lipid vesicles stabilized with chitosan did not display any notable differences in their hematological and biochemical profile compared to control animals. These data correlated with the histological results, which showed the absence of architectural changes in the examined tissues. Biological in vitro and in vivo evaluation revealed that the microvesicles containing diclofenac are biocompatible, with potential to be used as delivery systems to modify the drug release, thus making them an attractive candidate for biomedical applications.